Interstate Variation in the Mathematics Achievement of Rural and Nonrural Students - Jaekyung Lee; Walter G. McIntire (Journal of Research in Rural Education, 2000)
This study challenges our monolithic view ofrural education through a systematic analysis comparing 'rura! and nonrural student achievement and schooling conditions in the nation and states participating in the 1992 and 1996 NAEP eighth grade mathematics assessments. The results show that while rural and nonrural students had comparable levels of math achievement in 1992, by 1996 rural students overall had begun to outperform their nonrural counterparts. However, the achievement gaps varied considerably from state to state, with rural students performing significantly better in some states and significantly poorer in others. The differences and gains appear to be explained by variance in a broad range ofschoolingfactors (instructional resources, advanced course offerings, progressive instruction, professional training, safe/orderly climate, collective support). The results have important implicationsfor comprehensive school reform efforts as we attempt to improve education for all our students, particularly those in our rural schools.